1927 Haw. Sess. Laws 236 - (:unkn) unknown (My University, 1927)
An Act . . . Relating to the Discharge of Firearms and other Weapons upon Public Highways, § 1: Prohibited the discharge on the public highways with a firearm or other weapon capable of causing death or inflicting serious personal injury, including air-guns and sling-shots. Violators guilty of a misdemeanor, punishable by fine of not less than ten nor more than two hundred and fifty dollars, or imprisonment not more than one year, or both fine and imprisonment.
Keywords: DISCHARGE